Background Knowledge in Intercultural Communication of Media Spanish and Ukrainian Languages - Бокова, Поліна (Київський національний університет імені Тараса Шевченка, 2023)
The article examines the phenomenon of background knowledge, its place and role in the process of intercultural communication. The current stage of development of the world community opens up new opportunities for cultural and intercultural communication, which today is interpreted as communication between representatives of different cultures, involves mutual understanding of the participants of the communicative act belonging to different national cultures. It is also noted that there are a certain number of problems between representatives of different cultures and speakers of different languages, which are directly related to the most important component of intercultural communication, which includes the languages and cultures involved in this process. Culture is a set of material and spiritual values accumulated in one or another national community that are absent in another or significantly different from them, make up the national socio-cultural fund, which is reflected in the language. Background knowledge is considered as socio-cultural information that is characteristic of a certain nation, learned by the mass of its representatives and reflected in the language of this national community. They are a key component of our perception, they actually precede knowledge about the subject and help to obtain new information about it, and serve as a factor in overcoming the linguistic and cultural barrier in intercultural communication. Thus, background knowledge is presented as a set of ideas about what makes up the real background against which the picture of the life of another country, another people un folds.

В статті розглядається феномен фонових знань, їх місце і роль в процесі міжкультурної комунікації. Сучасний етап розвитку світової спільноти відкриває нові можливості культурної і міжкультурної комунікації, яка сьогодні трактується як спілкування між представниками різних культур, передбачає взаєморозуміння учасників комунікативного акту, що належать до різних національних культур. Також зазначається, що між представниками різних культур і носіями різних мов існує певна кількість проблем, що безпосередньо пов’язані з найважливішим компонентом міжкультурної комунікації, який включає мови і культури які беруть участь в цьому процесі. Культура є сукупністю матеріальних і духовних цінностей накопичених в тій чи іншій національній спільноті які відсутні в іншій або суттєво відрізняються від них, складають національний соціокультурний фонд, що знаходить своє відображення в мові. Фонові знання розглядаються як соціокультурні відомості, які є характерними для певної нації, засвоєні масою її представників і відображені в мові даної національної спільноти. Вони є ключовим компонентом нашого сприйняття, фактично випереджають знання про предмет і допомагають отримати про нього нову інформацію і слугують фактором подолання лінгвокультурного бар’єру в міжкультурній комунікації. Таким чином, фонові знання представлені як сукупність уявлень про те, що складає реальний фон, на якому розгортається картина життя іншої країни, іншого народу.
Фонові знання в міжкультурній комунікації носіїв іспанської і української мов
Keywords: фонові знання; міжкультурна комунікація; культурі; ключовий компонент; соціокультурний; лінгвокультурний; background knowledge; intercultural communication; culture; key component; sociocultural; linguistic and cultural